2001
DOI: 10.1002/1097-0053(200101/02)12:2<45::aid-jcaf8>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

E-commerce strategies your shareholders will love

Abstract: Buying or merging with another company isn't the only way to maximize shareholder wealth. You can build your own e‐commerce business instead. But how can you structure your organization to accommodate the new operations, and address shareholder concerns at the same time? The authors suggest some effective strategies. © 2001 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The architectural models mentioned below are generally used in real-life applications [12,13]: Order Form Architecture and Web Server, Open Market Commerce Architecture and the Open Buying on the Internet (OBI) architecture.…”
Section: Electronic Commercementioning
confidence: 99%
“…The architectural models mentioned below are generally used in real-life applications [12,13]: Order Form Architecture and Web Server, Open Market Commerce Architecture and the Open Buying on the Internet (OBI) architecture.…”
Section: Electronic Commercementioning
confidence: 99%
“…In addition, business experience, education and training appear to have a positive correlation with business success (Hyungrae and Jinjoo, 1996;Simpson et al, 2004). Other studies have found that personal characteristics of leadership, high level of energy, passion, vision and risk taking are positively correlated with business success (Duncan, 1991;Hopkins, 2006;Landry and Jalbert, 2001).…”
Section: Introductionmentioning
confidence: 95%